Changes in antiviral susceptibility to entry inhibitors and endocytic uptake of dengue-2 virus serially passaged in Vero and C6/36 cells - Acosta, Eliana Gisela (2014)
The aim of the present study was to analyze the influence of virus origin, mammalian or mosquito cell-derived, on antiviral susceptibility of DENV-2 to entry inhibitors and the association of this effect with any alteration in the mode of entry into the cell. To this end, ten serial passages of DENV-2 were performed in mosquito C6/36 cells or monkey Vero cells and the antiviral susceptibility of each virus passage to sulfated polysaccharides (SPs), like heparin and carrageenans, was evaluated by a virus plaque reduction assay. After serial passaging in Vero cells, DENV-2 became increasingly resistant to SP inhibition whereas the antiviral susceptibility was not altered in virus propagated in C6/36 cells. The change in antiviral susceptibility was associated to a differential mode of entry into the host cell. The route of endocytic entry for productive Vero cell infection was altered from a non-classical clathrin independent pathway for C6/36-grown virus to a clathrin-mediated endocytosis when the virus was serially propagated in Vero cells. Our results show the impact of the cellular system used for successive propagation of DENV on the initial interaction between the host cell and the virion in the next round of infection and the relevant consequences it might have during the in vitro evaluation of entry inhibitors.